PS-B06-2: IN VIVO MYOCARDIAL EFFECTS OF INTRAPERITONEAL ARGLABIN VIA NLPR3 INFLAMMASOME AND MAPK/IKKB;/NFKB PATHWAYS. (January 2023) - Bisht, Khushboo; Arya, Dharam Vir Singh; Verma, Vipin Kumar; Abdullah, Zia; Ray, Ruma; Narang, Rajiv; Nag, Tapas Chandra; Bhatia, Jagriti
Abstract : Introduction: Myocardial injury is a consequence of multiple underlying events that lead immune response by activated immune cells. Oxidative stress triggers an inflammatory cascade and apoptosis, this exacerbates cardiac injuries and dysfunction. Arglabin is a sesquiterpene lactone, an anticancer compound shown to have potential anti-diabetic effects in in vivo model. Methods: Male Wistar Rats in the 6 out of 9 groups were pre-treated with different doses (2.5 μg/kg, 5 μg/kg and 10 μg/kg of Arglabin) for 21 days. other 3 groups were normal control, vehicle and isoproterenol control. On 22nd day, isoproterenol was injected to induced myocardial injury (85 mg/kg/day). Normal control and isoproterenol control groups. Histopathological examination, electron microscopy, biomarkers (cTnI and LDH), cardiac parameters, oxidative stress (MDA, GSH, SOD, and CAT), inflammatory mediators (IL-6, IL-1β;, and TNF α), and apoptotic markers (BAX, Bcl2, and caspase-3) were evaluated. Results: Histopathological examination revealed increased neutrophilic infiltration in arglabin pretreated groups that correlated with electron microscopic findings. increased activity of IL-6, IL-1β;, TNFα, Caspase-1, caspase-3 and BAX was found in different pre-treated group. increased JNK expression was observed in arglabin pre-treated groups (2.5, 5, 10). altered expression of NFκB, P38, pP38 and IKKβ; were observed. Conclusion: Arglabin administration altered myocardial structure and modulated myocardial function via NLRP3 and MAPK pathway. Consideration regarding cardiovascular adverse effects must be undertaken when exploring other potential role of arglabin. Also, continuous cardiovascular monitoring is suggested for those on anti-cancer treatment with arglabin.